Real-life efficacy of immunotherapy for Sézary syndrome: a multicenter observational cohort studyResearch in context - Alizée Bozonnat; Marie Beylot-Barry; Olivier Dereure; Michel D’Incan; Gaëlle Quereux; Emmanuella Guenova; Marie Perier-Muzet; Stephane Dalle; Florent Grange; Manuelle-Anne Viguier; Caroline Ram-Wolff; Laurence Feldmeyer; et al. (EClinicalMedicine, 2024)
Summary: Background: Sézary syndrome is an extremely rare and fatal cutaneous T-cell lymphoma (CTCL). Mogamulizumab, an anti-CCR4 monoclonal antibody, has recently been associated with increased progression-free survival in a randomized clinical trial in CTCL. We aimed to evaluate OS and prognostic factors in Sézary syndrome, including treatment with mogamulizumab, in a real-life setting. Methods: Data from patients with Sézary (ISCL/EORTC stage IV) and pre-Sézary (stage IIIB) syndrome diagnosed from 2000 to 2020 were obtained from 24 centers in Europe. Age, disease stage, plasma lactate dehydrogenases levels, blood eosinophilia at diagnosis, large-cell transformation and treatment received were analyzed in a multivariable Cox proportional hazard ratio model. This study has been registered in ClinicalTrials (SURPASSe01 study: NCT05206045). Findings: Three hundred and thirty-nine patients were included (58% men, median age at diagnosis of 70 years, Q1-Q3, 61–79): 33 pre-Sézary (9.7% of 339), 296 Sézary syndrome (87.3%), of whom 10 (2.9%) had large-cell transformation. One hundred and ten patients received mogamulizumab. Median follow-up was 58 months (95% confidence interval [CI], 53–68). OS was 46.5% (95% CI, 40.6%–53.3%) at 5 years. Multivariable analysis showed that age ≥ 80 versus <50 (HR: 4.9, 95% CI, 2.1–11.2, p = 0.001), and large-cell transformation (HR: 2.8, 95% CI, 1.6–5.1, p = 0.001) were independent and significant factors associated with reduced OS. Mogamulizumab treatment was significantly associated with decreased mortality (HR: 0.34, 95% CI, 0.15–0.80, p = 0.013). Interpretation: Treatment with mogamulizumab was significantly and independently associated with decreased mortality in Sézary syndrome. Funding: French Society of Dermatology, Swiss National Science Foundation (IZLIZ3_200253/1) and SKINTEGRITY.CH collaborative research program.